Wheat Escapes Low Light Stress by Altering Pollination Types - Yang, Hong; Li, Yongpeng; Li, Dongxiao; Liu, Liantao; Qiao, Yunzhou; Sun, Hongyong; Liu, Wenwen; Qiao, Wenjun; Ma, Yuzhao; Liu, Mengyu; Li, Cundong; Dong, Baodi (Frontiers in Plant Science, 2022)
Although low light stress seriously affects florets fertility and grain number during the reproductive period, crops can be fertilized by heterologous pollen to alleviate the reduction of grain number. However, wheat is strongly autogamous, how to change to outcross after low light remains unclear. To understand the mechanisms of this change process, an approach combined morphological, physiological, and transcriptomic analyses was performed under low light stress imposed at the young microspore stage (the booting stage from tetrad to uni-nucleate microspores stage). The results showed that low light stress caused pollen abortion, and the unfertilized ovary is fertilized by heterologous pollen after floret opening. Compared to control, the opening angle of lemma and glume were increased by 11.6%-48.6% and 48.4%-78.5%, respectively. The outcross of stressed wheat compensated for the 2.1%-18.0% of grain number loss. During this process, phytohormones played an important role. Jasmonic acid (JA) and methyl jasmonate (MeJA) levels in spikelets were increased. Meanwhile, lignin and cellulose content decreased, and genes associated with cell wall related GO terms were enriched. Among the differentially expressed genes (DEGs), were identified 88-710 transcription factors genes, of which some homologs in Arabidopsis are proposed to function in lignin and cellulose, influencing the glume and lemma opening. Our finding can provide new insight into a survival mechanism to set seeds through pollination way alteration in the absence of self-fertilization after the stress of adversity.